2016
DOI: 10.1111/ipd.12273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of chlorhexidine and miswak extract on the clinical performance and antibacterial properties of conventional glass ionomer: an in vivo study

Abstract: The addition of CHX and miswak to GIC showed superior antibacterial properties than conventional GIC, without seriously affecting the clinical performance of the restoration until the 6-month follow-up, but failure significantly increased in terms of marginal defects at 9 months with CHX (group 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
5
22
1
3
Order By: Relevance
“…A recent study showed that the addition of 0.5% CHX to GIC improved antibacterial properties compared to conventional GIC, without affecting the clinical performance of class I restorations in young permanent molars until the 3-month follow-up. However, in contrast to our results, after 9 months the restoration success with GIC containing CHX (60%) was lower than the control group (85%) 14 . Differences of age, type of dentition and restorative material used could explain the disparities found in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent study showed that the addition of 0.5% CHX to GIC improved antibacterial properties compared to conventional GIC, without affecting the clinical performance of class I restorations in young permanent molars until the 3-month follow-up. However, in contrast to our results, after 9 months the restoration success with GIC containing CHX (60%) was lower than the control group (85%) 14 . Differences of age, type of dentition and restorative material used could explain the disparities found in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Glass-ionomer cements (GICs) have important properties for applications as restorative materials, such as the ability to chemically adhere to the enamel and dentin, low thermal expansion coefficient, and biocompatibility [6][7][8]. On the other hand, these materials show disadvantages like low wear and fracture resistance, making them unsuitable for applications in posterior-tooth restorations [9][10][11]. Another limitation of GIC includes high microleakage in sandwich restorations where phosphoric acid etching of GIC prior to the placement of composite resin does not improve the sealing ability of sandwich restorations [12].…”
Section: Introductionmentioning
confidence: 99%
“…A odontologia minimamente invasiva tem enfatizado a preservação máxima do tecido durante manejo de lesões profundas de cárie dentinária. A remoção seletiva da dentina é recomendada com o intuito de preservar ao máximo a estrutura dentária e evitar uma possível exposição pulpar (Kabil et al, 2017;Ornellas et al, 2018). Nesse sentindo, a completa vedação da cavidade é capaz de promover a redução bacteriana após um determinado período de tempo e viabilizar a remineralização na dentina afetada dependendo do material utilizado, desempenhando, assim, um papel relevante no sucesso do tratamento (Melo et al, 2015;Pinheiro et al, 2018;Ornellas et al, 2018).…”
Section: Lesões De Cárie Em Dentinaunclassified
“…A selagem ideal da cavidade aumenta a longevidade das restaurações dentárias ao cortar o suprimento de nutrientes bacterianos, impedindo assim a progressão da lesão cariosa. Entretanto, recorrência de cárie e sensibilidade pósoperatória podem ocorrer devido à presença de microrganismos viáveis após o preparo cavitário (Pinheiro et al, 2018;Kabil et al, 2017;Melo et al, 2015).…”
Section: Lesões De Cárie Em Dentinaunclassified